Characteristics and potential values of bio-oil, syngas and biochar derived from Salsola collina Pall. in a fixed bed slow pyrolysis system. (November 2016) - Yue, Yan; Lin, Qimei; Irfan, Muhammad; Chen, Qun; Zhao, Xiaorong
Highlights: Salsola collina Pall. was a newly-reported halophyte to be utilized by pyrolysis. Biochar produced at 500 °C had the highest EC, K +, Na + and surface area. Biochar produced at 700 °C had the highest aromaticity, pH and CEC. The properties of biochar were relatively stable at 500 °C. Abstract: Salsola collina Pall. as a typical euhalophyte was slowly pyrolyzed at 300 °C, 500 °C and 700 °C in a fixed-bed system. The physiochemical properties of syngas, bio-oil and biochar were assayed to understand the impact of pyrolysis temperature on these parameters and then to evaluate their potential values. The results showed that syngas yield (26.07–46.37%) increased with pyrolysis temperature, while biochar yield (47.54–26.83%) decreased. Bio-oil yield (26–30%) was hardly affected by pyrolysis temperature. Both syngas and bio-oil had poor values as direct fuel. The euhalophyte-derived biochar had higher aromaticity (H/C 0.16–0.85, O/C 0.06–0.26), higher cation exchange capacity (198.82–435.74 cmol kg −1 ), and higher K + (59.35–80.42 g kg −1 ) and Na + (37.56–53.26 g kg −1 ) compared with glycophyte-derived biochars. Our findings imply that halophyte biochar may be more suitable to use as a soil conditioner, which is worthy of further study.